Analisis Hubungan Panjang Berat Pada Ikan Selar Kuning Selaroides leptolepis di Pangkalan Pendaratan Ikan (PPI), Kota Sorong - Yanti, Dwi Indah Widya; Masengi, Melisa; Penina Palemba, Yolda (Politeknik Negeri Sambas, 2023)
Sorong City is located in a strategic area in Southwest Papua Province. The development of the fisheries sector in Sorong City is increasing, and various efforts are being made by the Regional Government, one of which is to support Fish Landing Base (PPI) facilities that are needed by fishermen as a place to land their catch, which is then purchased by collectors or consumers. The types of fish that are generally landed in PPI Sorong City are generally large, medium, and small pelagic fish. Yellow trevally (Selaroides leptolepis), known locally as Oci fish, is one of the most popular fish types in Sorong. This study aimed to determine the relationship between the length and weight of yellow trevally (Selaroides leptolepis) as a basis for fisheries resource management. The research was conducted at PPI Sorong City in July, August, and September 2022. The samples used were obtained from Selar Fish landed in PPI Sorong City, which were then measured and weighed. The results obtained in July were b= 2.32, which was negative allometric; in August, b= 2.60, which was negative allometric; and in September, b= 3.10, which was positive allometric.